2017
DOI: 10.1038/srep43291
|View full text |Cite
|
Sign up to set email alerts
|

Compact, cost-effective and field-portable microscope prototype based on MISHELF microscopy

Abstract: We report on a reduced cost, portable and compact prototype design of lensless holographic microscope with an illumination/detection scheme based on wavelength multiplexing, working with single hologram acquisition and using a fast convergence algorithm for image processing. All together, MISHELF (initials coming from Multi-Illumination Single-Holographic-Exposure Lensless Fresnel) microscopy allows the recording of three Fresnel domain diffraction patterns in a single camera snap-shot incoming from illuminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…Lensless or singlet lens imaging setup is the simplest imaging system, which is very attractive in portable microscopy and field practices . Although diffraction‐based lensless microscopy works well, its imaging mechanism results in short working distance which means the bio‐sample must be very close to the CCD/CMOS image sensors .…”
Section: Introductionmentioning
confidence: 99%
“…Lensless or singlet lens imaging setup is the simplest imaging system, which is very attractive in portable microscopy and field practices . Although diffraction‐based lensless microscopy works well, its imaging mechanism results in short working distance which means the bio‐sample must be very close to the CCD/CMOS image sensors .…”
Section: Introductionmentioning
confidence: 99%
“…Electron holography today is a mature research field and widely in use, allowing for molecular imaging [9,10]. Digital holography within the visible wavelength regime has attracted considerable attention where a broad spectrum of light sources has been employed, ranging from gas [11,12], solid state [13] and semiconductor [1,14,15,16] lasers over light emitting diodes (LEDs) [17,18,19,20] to halogen lamps [21]. Recently, ultra-broadband digital holography with sunlight illumination has been demonstrated, employing a new reconstruction algorithm [22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lens-based DOAH has recently been employed in in-line industrial production control [40] and for imaging of semiconductor structures [41]. In life-sciences, DIHM has the advantage of working label-free, which enables non-invasive, in-vivo study of biological samples, for example RBCs [42,43,44], parasited mouse RBCs [45], sperm cells [15], diarrhea parasites [17], and several aquatic organisms [38]. Moreover, as information about the whole sample volume is encoded in one single hologram, processing speed is substantially increased as compared to microscopic scanning techniques such as confocal or fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies show similar results. Ibáñez-Sanz et al reported a discriminatory accuracy value of 0.63 for CRC risk prediction model combining some modifiable risk factors (alcohol, obesity, physical activity, red meat and vegetable consumption, and nonsteroidal anti-inflammatory drug use), family history of CRC, and a GRS based on 21 susceptibility SNPs [7]. More recently, Weigl et al [8] derived a GRS based only in a significant number of common variants (48 SNPs) previously associated with CRC.…”
mentioning
confidence: 99%